2009
DOI: 10.1111/j.1748-0361.2009.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Rurality and Other Determinants of Early Colorectal Cancer Diagnosis in Nebraska: A 6‐Year Cancer Registry Study, 1998‐2003

Abstract: Early CRC diagnosis needs to be increased in rural (non-core) non-metropolitan residents, unmarried residents, and those with private insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
6
15
0
Order By: Relevance
“…7 Furthermore, colon cancer tends to be diagnosed at later stages in rural patients. 810 We have previously explored the impact of the location of treatment on outcomes, specifically demonstrating that treatment at a rural hospital did not confer worse surgical mortality except for in patients with complex cancers. 11 However, an effective appraisal of quality cancer care should more broadly consider the structures, processes and outcomes of cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, colon cancer tends to be diagnosed at later stages in rural patients. 810 We have previously explored the impact of the location of treatment on outcomes, specifically demonstrating that treatment at a rural hospital did not confer worse surgical mortality except for in patients with complex cancers. 11 However, an effective appraisal of quality cancer care should more broadly consider the structures, processes and outcomes of cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…With major medical centres being concentrated in densely populated urban centres, it has been suggested that rural and remote locations may be associated with poorer access to screening and specialised health care (Parikh-Patel et al , 2006; Heathcote and Armstrong, 2007). However ecological studies have presented a mixed picture in terms of SES (Parikh-Patel et al , 2006; Frederiksen et al , 2008; Henry et al , 2009; Booth et al , 2010) and geographic remoteness (Fazio et al , 2005; McLafferty and Wang, 2009; Sankaranarayanan et al , 2009) in stage at diagnosis.…”
mentioning
confidence: 99%
“…Other studies imputed stage information [15,19], or analysed missing stage as a separate group [35]. Average stage at diagnosis varied by tumour site [38], histological type for ovarian cancer [20], and by subsite for colorectal cancer [33]. …”
Section: Resultsmentioning
confidence: 99%
“…Average stage at diagnosis varied by tumour site [38], histological type for ovarian cancer [20], and by subsite for colorectal cancer [33]. …”
Section: Resultsmentioning
confidence: 99%